Bresek Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Two half brothers with a new syndrome of brain anomalies, retardation, ectodermal dysplasia with alopecia, skeletal malformations, ear abnormalities, and kidney dysplasia (BRESEK) are reported from the University of Minnesota, Minneapolis.